MICA polymorphisms associated with antithyroid drug‐induced agranulocytosis in the Chinese Han population - Gong, Xiaojuan (Immun Inflamm Dis, 2020)
BACKGROUND: Graves' disease (GD) is a clinical autoimmune thyroid disease. During the treatment of GD, antithyroid drug‐induced agranulocytosis (TIA) is a common and even life‐threatening adverse drug reaction. Previous studies suggested that susceptibility to TIA is strongly associated with HLA‐B*27:05, HLA‐B*38:02, and HLA‐DRB1*08:03 genetic variation and six single nucleotide polymorphisms (SNPs) in MICA genes. AIMS: The purpose of this study is to further study the associations between TIA, HLA‐B and MICA. MATERIALS & METHODS: We genotyped MICA‐STR and MICA‐129 variants in 41 TIA and 308 control patients with GD and investigated the linkage effect among SNPs and short tandem repeat (STR) of MICA and HLA‐B alleles. RESULTS: The results showed that MICA*A5.1 was significantly associated with TIA (p = .007, odd ratio = 1.958, 95% confidence interval, 1.192–3.214). In addition, high linkage among MICA‐129 and six SNPs MICA and HLA‐B was detected, and two haplotypes (AAAACAAAAACGGCCTA and AACAAAAAAAACATTAA (p = 5.14E−07 and p = 3.42E−08, respectively)) were significantly associated with TIA. Furthermore, when we analyzed only MICA‐129 and HLA‐B separately, the haplotypes (AAAACAAAAAA with p = 2.49E−07 and AACAAAAAAAA with p = 2.14E−09) were identified with more significant effects. MICA‐129 was completely linked to six SNPs with haplotypes ACATTACA (p = 2.05E−05) significantly associated with TIA. CONCLUSION: These data indicated that there was a significant linkage effect between MICA‐129 and other alleles, suggesting that they exert interactive effects as risk factors for the development of TIA.